Whale watching in Brazil (Sustainability in Debate, 2022)
This study aims to investigate whale-watching in Brazil, based on a survey of their areas of occurrence, key species and current rules and regulations. The methodology includes an extensive literature review on areas where cetaceans occur in Brazil, dolphin and whale-watching, legal instruments and codes of conduct for the planning of this activity. A search for reference areas for whale watching was carried out on the homepage of tour operators and agencies. Data collection took place through phone contact, e-mail and social networks of agencies and tour operators. In this study, seven key cetacean species for ecotourism were identified, 29 reference areas, with 79% included in Protected Areas. The results of this study will be able to support actions of monitoring and inspection of whale-watching, aiming at its management and the protection of these animals.